The Role of Sulfur in Solution‐Processed Cu2ZnSn(S, Se)4 and its Effect on Defect Properties. (16th October 2012) - Duan, Hsin‐Sheng; Yang, Wenbing; Bob, Brion; Hsu, Chia‐Jung; Lei, Bao; Yang, Yang
Abstract Understanding the electrically active defects in kesterite Cu2ZnSn(S, Se)4(CZTSSe) is critical for the continued development of solar cells based on this material, but challenging due to the complex nature of this polycrystalline multinary material. A comparative study of CZTSSe alloys with three different bandgaps, made by introducing different fractions of sulfur during the annealing process, is presented. Using admittance spectroscopy, drive level capacitance profiling, and capacitance‐voltage profiling, the dominant defect energy level present in the low sulfur content device is determined to be 0.134 eV above the valence band maximum, with a bulk defect density of 8 × 1014 cm−3, while the high sulfur content device shows a deeper defect energy level of 0.183 eV and a higher bulk defect density, 8.2 × 1015 cm−3. These findings are consistent with the current density–voltage characteristics of the resulting solar cells and their external quantum efficiency. It suggests that as the sulfur content increases, the bandgap of the absorber is enlarged, leading to an increasing open‐circuit voltage (Voc), that is accompanied by stronger recombination due to the higher defect density of the sulfur‐rich absorber. This is reflected in large Voc deficit and poor carrier collection of the high sulfur content device.